K-Pop Business: Prospects and Challenges for Entrepreneurs in Indonesia - S O Putri (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this research is to find out how K-Pop popularity is turned into a business for entrepreneur in Indonesia. Nowadays people are crazy about Hallyu or Korean Wave, including the K-dramas and K-pop, South Korean music. The market size of the South Korean entertainment is getting bigger and there are over 100 million members of Korean Wave fan clubs in many countries around the world in 2021. The research method was qualitative methods, with data collection techniques through literature studies The results showed that the K-Pop business in Indonesia opens many opportunities for entrepreneurs in developing business by utilizing the popularity of K-Pop. The hype around K-Pop bands and other celebrities has led many fans to spend a lot of money on their idol merchandise. Though the pandemic of Covid-19 has affected the economy, but the popularity of Korean Wave is growing in Indonesia. Many young entrepreneurs are starting small Hallyu businesses by utilizing social media and e-commerce. Although it is economically valuable, there are challenges faced by the entrepreneurs, namely intellectual property rights.